Genetic diversity of local irrigated rice (Oryza sativa L.) - Islam, MZ; Akter, K; Rashid, ESMH; Khalequzzaman, M; Bashar, MK (Bangladesh Journal of Plant Breeding and Genetics, 2011)
Bangladesh Journal of Plant Breeding and Genetics, Vol.22(2) December 2009 51-56